Nghiên cứu ảnh hưởng của nhiệt độ đến phản ứng khâu mạch nhựa epoxy biến tính dầu đậu nành bằng dianhydrit piromelitic và tính chất của màng khâu mạch - Hiền, Lê Xuân; Ngọc Mai, Đỗ Thị (Vietnam Journal of Chemistry, 2014)
The influence of the temperature on the crosslinking of soyabean oil modified epoxy resin (ESO) by dianhydrite piromelitic (DAP) in presence of the dimetylbenzylamin (DMBA) has been studied and the optimal conditions for the curing have been determined. It was showed that at the optimal conditions: Equal mol of epoxy and anhydrite groups, reactions temperature and duration 120 oC and 90 min, respectively, the DMBA content of 2.31 % of the total mass of ESO and DAP, the epoxy and anhydrite groups had been totally converted, led to formation of a cured coating with gel fraction 85 %, swelling degree 160 %, pencil harness HB, impact resistance 200 kG.cm, flexibility 1 mm, gloss at 60o 75 %, adhesion 0 point. Keywords: Epoxy resin, soyabean oil, dianhydrite piromelitic, curing.